(untitled) (Al-Qamar, 2025)
It is great virtues to comprehend the revealed book of Allah, such kind of narrations are called Exegesis of Holy Quran. There are few narrators, who adopted coherence aptitude in Quran very simply and briefly. They had claimed that Quranic chapters as well as verses are mutually connected. this kind of contact is named as” Nazm-i-Quran”. Molana Ali Ibnn Ahmed al-Muhaimi was a Mufasir-i Quran, he the blessed one, wrote a tafsir named Tabseer-ur-Rehmān wa Tasseer-ur- Mannān” the methodology of tafsir also represents the ideology of coherence. The tafaseer was published by Maktaba Bolāq Egypt. List of the methodology found in this tafsir is as under: 1. Every surah has a basic claim, verses of that surah surround about that theme. 2. Tawheed is the principal commandment discussed in the whole Quran. 3. Coherence is the miracle of Quran. 4. The whole Quranic Surahs are as connected as pearls. 5. Quran is a sermon style book, not like a written one.